The evaluation of the contribution of low frequency, intermediate penetrance sequence variants to the pathogenesis of Type 2 Diabetes - Jafar-Mohammadi, B (2012)
Genome wide association studies (GWAS) and their subsequent meta-analysis have identified a large number of susceptibility variants for Type 2 diabetes (T2D) risk. However, the familial aggregation seen in this disease is not yet fully explained. The sibling relative risk (λs) due to all known variants is ~1.104 which is well below the epidemiological estimates of λs of ~3.0. There has therefore been great interest in the potential role of variants that would have been largely invisible to the initial wave of GWAS and linkage approaches. Low frequency (minor allele frequency 1-5%), incompletely penetrant (odds ratio 2-4) variants (LFIP), are one such group of potential susceptibility variants. The overall objective of this project (designed and implemented in 2007-2010) was to evaluate the contribution of LFIP variants to the inherited susceptibility to T2D. I tested the specific hypothesis that genes already-implicated in diabetes pathogenesis (due to an established role in monogenic or multifactorial disease) also harbour LFIP variants, and that those variants may contribute appreciably to the prediction of disease risk. Mutations in exons only encoding isoform-A of HNF1A have been demonstrated to lead to a later age of diagnosis of HNF1A-MODY. This region was therefore felt to be auspicious for harbouring LFIP variants impacting on T2D risk. I have demonstrated that such variants impacting on T2D risk are unlikely to be present in this region by use of Sanger sequencing in a sample enriched for young onset, familial T2D. The role in T2D risk of candidate LFIP variants across 5 genes (HNF1A, HNF4A, PDX1, KCNJ15 and LARS2), was evaluated by large scale association studies. For one variant, T130I of HNF4A, a modest association (p=5x10-4) with T2D was seen in UK samples and the strength of association was marginally improved by incorporation of all previous studies of this variant in T2D in a meta-analysis (p=2.1x10-5). This study demonstrated the difficulties encountered in confirming the association of low frequency variants to complex diseases, especially for those with modest effect sizes. At the time of project design and inception “next-generation” sequencing platforms were in their infancy and the study design I planned (that of pooled, targeted sequencing) had not been widely applied. It was therefore necessary to design and optimise protocols for sample preparation for sequencing on this platform. I used the Genome Analyzer II platform to sequence ten genes previously implicated in T2D or monogenic diabetes pathogenesis in pooled DNA samples. This approach yielded in excess of 2900 variants, a large portion being novel. As part of this project I have highlighted heuristics that can be used in the follow-up of potential susceptibility variants discovered using high throughput sequencing. I have also established protocols and pathways for sample preparation that can be utilised across several next generation sequencing platforms for future studies in the host institution and beyond.